Pengaruh Kepuasan Konsumen Terhadap Kinerja Karyawan Pada Outtlet Chattime di Kota Karawang - Putri Ayu Rukmini; Puji Isyanto; Dini Yani (Nanggroe: Jurnal Pengabdian Cendikia, 2023)
Until now, Chatime has been able to maintain its existence and even become a Top Brand for five consecutive years among other drinks that have existed longer than Chatime. This study uses a quantitative method that is influential, namely to determine the effect of consumer satisfaction on employee performance at chattime outlets in the city of Karawang. Sampling was carried out using probability sampling technique, namely simple random sampling with a sample of 30 people. By using multiple analysis and hypothesis testing by providing a questionnaire given to consumers. Based on the results of research conducted that Employee Performance has a positive and significant effect on Chattime Consumer Satisfaction in the city of Karawang. This can be proven by the value of T Count (7.107) > T- Table (2.051) and then the coefficient of determination from the results of the hypothesis test, obtained R-Square 0.643 which explains 64.3% Consumer Satisfaction and the rest is influenced by other factors outside the research This. Based on the results of these studies, the authors can conclude that the hypothesis approved by the research is accepted